A Real Orthogonal Space-Time Coded UWB Scheme for Wireless Secure Communications. (13th September 2009) - Zhang, Yanbing; Dai, Huaiyu
Abstract : Recent research reveals that information security and information-hiding capabilities can be enhanced by proper exploitation of space-time techniques. Meanwhile, intrinsic properties of ultra-wideband (UWB) signals make it an outstanding candidate for secure applications. In this paper, we propose a space-time coding scheme for impulse radio UWB systems. A novel real orthogonal group code is designed for multi-antenna UWB signals to exploit the full spatial diversity gain and achieve the perfect communication secrecy. Its performance in a frequency-selective fading channel is analyzed. The transmission secrecy, including low probability of detection (LPD), low probability of intercept (LPI), and anti-jamming performance, is investigated, and some fundamental tradeoffs between these secrecy metrics are also addressed. A comparison of the proposed scheme with the direct sequence spread spectrum (DSSS) technique is carried out, which demonstrates that proper combination of UWB and space-time coding can provide substantial enhancement to wireless secure communications over other concurrent systems.